Applying Psychological and Educational Health Models to Determine the Effect of Cognitive and Behavioral Interventions on Tuberculosis Treatment Outcomes in Plateau State, Nigeria - Comfort Nanbam Sariem; Maxwell Patrick Dapar; Nenman Musa Lenka; Jacob Kolawole; John Aguiyi (University of Minnesota Libraries Publishing, 2022)
Background: The prolonged multi-drug treatment regimen for tuberculosis (TB) can lead to non-adherence and unsuccessful treatment outcomes. Educational and psychological health models can be used to design cognitive and behavioral interventions to improve adherence and treatment outcomes. Objective: To determine the effect of cognitive and behavioral interventions on TB treatment outcomes. Methods: The quasi-experimental study conducted in six TB treatment centers involved reinforced medication education and adherence counseling (MEAC), designed from a structured validated psychometric scale. Data were collected three different times during the intensive and continuation phases of treatment from 463 TB patients (232 in the control and 231 in the intervention group). Baseline demographic and clinical characteristics were compared between the groups. The generalized estimating equation model was used to analyze the repeated measures by determining if treatment success was associated with the cognitive and behavioral interventions and medication adherence. Results: The males made up 290(62.6 %) of the population. The mean age was 36.75±13.9. Most of the TB patients were newly diagnosed 413(89.2%) and HIV negative 315(68%), with secondary level of education 216(46.6%). There was no significant difference in baseline characteristics between the groups. The intervention group was four times more likely to have treatment success (p<0.01; CI=1.5-8.4), compared to the control group. Medication-adherent TB patients were 24 times more likely to have treatment success than patients who did not adhere (p<0.001; 10.8-52.1). TB patients' emotions, attitudes, and perceptions of their medicines were predictors of treatment success (p<0.05; 1.0 - 1.1). Conclusion: The cognitive and behavioral interventions administered to TB patients improved successful treatment outcomes.